Explorations in George Eliot’s Perception of Islam: Arabs, Moors, Muslims, and Islam in The Spanish Gypsy - Chenni , Dallel (Journal of Human Sciences, 2023)
This article proposes to explore George Eliot’s perception of Islam and Muslims in The Spanish Gypsy (1868). It argues that Eliot showed prejudiced views against this religion and its followers at the time she was writing this poem. This will be demonstrated through her use of typically stereotyped racial characterization and persistent ostentatious religious iconography amid a narrative context exacerbated by violence and cruelty as shown in the story of the poem set in the fifteenth-century al-Andalus’ (Moorish Spain) holy war. In order to clearly determine Eliot’s attitude to Muslims as the alien others, the article will equally  explore and compare her view with other ethnic and religious communities involved in the historical course of events described in the poem, notably Gypsies, Jews and Christians.